2007
DOI: 10.4028/www.scientific.net/msf.546-549.433
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Microstructure and Mechanical Property of High Strength Mg-Nd-Zn-Zr Alloy

Abstract: The microstructure and mechanical properties of Mg-3wt%Nd-0.2wt%Zn-0.4wt%Zr alloy in as-cast, solution-treated and solution-treated + peak-aged were investigated. The alloy had a cast structure with large intergranular Mg12Nd phase between the α-Mg matrix. After solution-treated, the intergranular Mg12Nd phase disappeared and lots of small Zr-containing particles distributed inside the grains. Small plate-like phases precipitated inside the grains strengthened the alloy to a high level after peak-aged at 200°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Mg-RE alloy always contain 0.4-0.6wt% zirconium as grain refiner, such as WE43, WE54 [4]. With 0.2 wt% Zn and 0.4 wt% Zr added to Mg-3wt%Nd, high strength Mg-Nd-Zn-Zr alloy is got [5]. Mg-RE alloy are usually used as T6 state [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mg-RE alloy always contain 0.4-0.6wt% zirconium as grain refiner, such as WE43, WE54 [4]. With 0.2 wt% Zn and 0.4 wt% Zr added to Mg-3wt%Nd, high strength Mg-Nd-Zn-Zr alloy is got [5]. Mg-RE alloy are usually used as T6 state [4].…”
Section: Introductionmentioning
confidence: 99%
“…%) and low solubility at room temperature (~ 100 ppm), which make it suitable for potential age hardening [8]. The strength of age-hardened Mg-Nd alloys can be further enhanced through solid solution strengthening by controlled addition of third element such as zinc (Zn) [9,[10][11][12][13][14]. Researches have shown that addition of 0.2 wt.…”
Section: Introductionmentioning
confidence: 99%
“…% Zn to Mg-3 Nd wt. % alloy improves the mechanical properties through mainly solid solution strengthening mechanism [8,[12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Addition of trace amounts of element Zn to Mg-Nd alloy could further increase its peak aged hardness. [5][6][7] With increases in demand, the development of higher mechanical properties of Mg-Nd alloy is proposed. Recently, it has been reported that adding the abundant heavy RE such as Gd to Mg-Nd alloy shows superior mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Mg–Nd alloys have significant strengthening effect at room and high temperature 24. Addition of trace amounts of element Zn to Mg–Nd alloy could further increase its peak aged hardness 57. With increases in demand, the development of higher mechanical properties of Mg–Nd alloy is proposed.…”
Section: Introductionmentioning
confidence: 99%